2011
DOI: 10.7150/ijms.8.470
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Serum Uric Acid and Spirometric Values in Participants in a Health Check: The Takahata Study

Abstract: Background: Tissue hypoxia induces the degradation of adenosine triphosphate, resulting in the production of uric acid (UA). Patients with chronic obstructive pulmonary disease (COPD) have been reported to have high serum levels of UA (sUA), compared with control subjects. However, the relationship between sUA levels and spirometric measures has not been investigated in detail in a general population.Methods: Subjects aged 40 years or older (n = 2,917), who had participated in a community-based annual health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 40 publications
(46 reference statements)
8
61
1
Order By: Relevance
“…The only significant difference between these groups was age (see the Results section). In addition, workers in public institutions and many companies did not participate in this research programme for reasons described previously [25]. Differences in type of employment, socioeconomic status or lifestyle, including vitamin B intake, between participants and nonparticipants may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only significant difference between these groups was age (see the Results section). In addition, workers in public institutions and many companies did not participate in this research programme for reasons described previously [25]. Differences in type of employment, socioeconomic status or lifestyle, including vitamin B intake, between participants and nonparticipants may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the institutional ethics committee and all participants gave written informed consent [2]. Cross-sectional analyses of spirometry data for subjects who were enrolled from 2004 to 2005 (n53165) have been reported previously [2,[25][26][27]. Enrolment of subjects continued through 2006, and the additional data for these subjects became available recently.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairment of pulmonary function reduces oxygen intake, resulting in tissue hypoxia which is more prominent during AECOPD. Serum uric acid levels have been associated with the presence of airflow obstruction in a general population in Japan [9], whereas a small cross-sectional study showed significant associations between serum uric acid to creatinine ratio and spirometry values and dyspnoea in COPD patients [10]. Despite the above evidence, to date, no study has evaluated the role of uric acid levels on admission for acute exacerbations of COPD on the outcome of exacerbation and the longterm survival and exacerbation frequency of COPD patients.…”
Section: Introductionmentioning
confidence: 98%
“…7 There is data regarding the significance of serum uric acid level among patients with COPD. [8][9][10][11][12] Serum uric acid has been proposed as a marker of impaired oxidative metabolism and an independent prognostic marker in several cardio-vascular disorders such as congestive heart failure [13][14] pulmonary hypertension 15 and myocardial infarction and its related complications. [16][17] There are other biomarkers also which helps in assessing severity of COPD [18][19] but they are not easily available and are costlier also.…”
Section: Introductionmentioning
confidence: 99%